The Dynamics of Holling Type IV Prey Predator Model with Intra- Specific Competition - Naji, Raid; Shalan, Rehab (Iraqi Journal of Science, 2024)
In this paper a prey-predator model involving Holling type IV functional responseand intra-specific competition is proposed and analyzed. The local stability analysis ofthe system is carried out. The occurrence of a simple Hopf bifurcation is investigated.The global dynamics of the system is investigated with the help of the Lyapunovfunction and poincare-bendixson theorem. Finally, the numerical simulation is used tostudy the global dynamical behavior of the system. It is observed that, the system haseither stable point or periodic dynamics.